Market Timing Analysis of Turkish Pension Funds Using Smooth Transition Models - Özdinçer, Begümhan; Özyıldırım, Cenktan (Bilgesel Yayincilik San & Tic Ltd, 2013)
This article investigates by applying the smooth transition autoregressive model whether pension fund managers can implement successfully market timing strategy to earn abnormal returns and analyze their risk return performances. Unlike the classical market timing models used extensively in the literature this regime switching model allows for a continuum of regimes without making restrictive assumptions as in the classical market timing models. The methodology allows for a better approximation of the pension fund managers' investment behavior The results show that funds that show non-linearity in their asset allocation cannot apply successful market timing strategies. Therefore it is not justifiable for pension fund investors to invest in these riskier funds to generate excess returns and pay higher management fees.
Keywords: Pension funds; Market timing; Smooth transition models